Radiofrequency catheter ablation-associated silent iatrogenic right ventricular pseudoaneurysm: a case report and literature review - Haruki, Shogo; Yamamoto, Hiroyuki (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRight ventricular pseudoaneurysm (RVP) encased by adjacent pericardial or scar tissue is rare but can be a fatal sequela of cardiac rupture. Differentiating between pseudoaneurysms and true aneurysms is important because they have different natural histories and require distinct treatments. Radiofrequency catheter ablation (RFCA) is a potential cause of RVP; however, RFCA-associated RVP incidence and management remain unclear.Case presentationAn 88-year-old woman with refractory paroxysmal supraventricular tachycardia was admitted to our hospital. We performed an electrophysiological study, which led to a final diagnosis of atrioventricular nodal reentrant tachycardia, for which successful RFCA was performed. On post-procedural day 2, echocardiography revealed a small right ventricular apical outpouching. Cardiac computed tomography angiography led to the correct diagnosis of RVP, which was successfully treated with surgical repair. The postoperative course was uneventful.ConclusionsWe describe a unique case of RFCA-associated apical RVP. This case highlights the importance of the potential risk of iatrogenic RVP and the value of cardiac computed tomography angiography in diagnosing RVP in patients with right ventricular outpouching.